Perlindungan Hukum Hak Tradisional Masyarakat Hukum Adat terhadap Tindakan Individualisasi Tanah Ulayat untuk Tujuan Komersial - Stivani Marantika Poro; Ali Imron; Wika Yudha Shanty (University of Merdeka Malang, 2021)
The 1945 Constitution of the Republic of Indonesia has a very large role as the foundation of all existing laws and regulations in Indonesia. Including regarding the respect and recognition of customary law community units whose traditional rights as long as their existence still exist. In this paper, one of the examples taken by the authoris the indigenous people in the eastern part of East Nusa Tenggara Province, namely the indigenous people of Pubabu. The existence of the Pubabu indigenous people is very critical because the recognition they get is very weak. This causes their customary rights to be in a complicated position when it comes to dealing with the state’s right tocontrol. The local government seems to interfere with the rights of indigenous peoples because it is in the interests of the state. This certainly should not be done. Therefore, so that customary rights are not disturbed, let alone eliminating the right to control the state, it is necessary to have restrictions as well as strong legal protection from both the Central Government and the Regional Government, this is aimed at achieving the welfare of the customary law community and protection of the people. human rights, policies related to indigenous peoples must also be aspirational.